Pengaruh Model Problem Based Learning melalui Pendekatan Deep Learning terhadap Keterampilan Kolaborasi Siswa Kelas III pada Mata Pelajaran Pendidikan Pancasila di SD Negeri Mranggen 02 Polokarto - Annisaa; I Made Ratih Rosanawati; Suwarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning model through a Deep Learning approach on the collaboration skills of third-grade students in the Pancasila Education subject at SD Negeri Mranggen 02 Polokarto. This study used a quantitative approach with a pre-experimental method in the form of a One Group Pre-Test Post-Test Design. The research sample consisted of 20 third-grade students determined through a saturated sampling technique. Data collected was carried out through a collaboration-skills questionnaire and documentation. The data obtained were analyzed through prerequisite test in the from normality test and homogeneity test followed by a Paired Sample t-Test. The results showed an increase in the mean collaborations-skills score of students from before treatment (pre-test) at 38,20 to after treatment (post-test) at 49,20, and based on the Paired-Sample t-Test the Sig. (2-tailed) value obtained was 0,000 < 0,05. Thus, it can be concluded that there effect of Problem Based Learning model through a Deep Learning approach on the collaboration skills of third-grade students in the Pancasila Education subject.